Building a Successful Palestinian State Security - Hunter, Robert E. (RAND Corporation, 2006)
Throughout the history of Arab-Israeli peace negotiations, security has been the most important-and most challenging-issue for Palestinians, Israelis, and their neighbors. This study examines key external security issues regarding the construction of a Palestinian state. Its proposals include a NATO-led international peace-enabling force and Israeli-Palestinian confidence-building measures.